Pengembangan Umkm Dan Ekonomi Kreatif Di Kecamatan Kepanjenkidul Kota Blitar Melalui Seminar Legalitas Usaha, Digital Marketing Dan HAKI - Mu’tasim Billah; Nurcholish Majid; Mahesa Bachtiar Maulana; Arfad Syauqi Hikam Al Jonet; Munirotul Wahyuningsih; Gandhi Yoga Pratama; Galuh Deliana Putri Murdani; Desy Fitria Agustiyani (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
MSME development service activities as a way or solution to increase people's purchasing power, which in turn can cover up from the economic crisis situation. The implementation method used is by holding a seminar on entrepreneurship and creative economy entitled